Construct stability in anterior open wedge osteotomy: assessing 3D-printed polylactic acid wedges against cortical bone - Hoffeld, Kai; Hockmann, Jan P.; Wahlers, Christopher; Eysel, Peer; Hackl, Michael; Oppermann, Johannes (Clinical biomechanics, 2025)
Background - This in-vitro biomechanical study aimed to assess whether using a wedge as a gap filler in anterior open wedge osteotomy of the proximal tibia reduces load on the screw-plate construct and to evaluate if a 3D-printed polylactic acid wedge offers similar biomechanical stability like a bone wedge. - Methods - Twenty-four cadaveric proximal tibiae were randomly assigned to one of three groups: TomoFix plate alone as control group, TomoFix plate with a bone wedge, and TomoFix plate with a 3D-printed polylactic acid wedge. The specimens were subjected to axial loads of 400 N, 800 N, and 1200 N for 1000 cycles. Compression depth and axial stiffness were measured to assess stability. - Findings - There were no significant differences in overall compression depth or axial stiffness between the groups (p > 0.05). At 1200 N, hinge fractures occurred in 6 of 8 specimens in the control group, compared to 0 of 8 in the wedge groups. Both bone and polylactic acid wedges improved construct stability, with the polylactic acid wedge performing comparably to the bone wedge. - Interpretation - Gap fillers, whether bone or polylactic acid wedges, may contribute construct stability in anterior open wedge osteotomy of the proximal tibia. The 3D-printed polylactic acid wedge may be biomechanically comparable to the bone wedge, suggesting its potential as an alternative in clinical applications.
Online veröffentlicht: 2. April 2025, Artikelversion: 4. April 2025
Gesehen am 04.06.2025